2017
DOI: 10.15436/2475-6245.17.016
|View full text |Cite
|
Sign up to set email alerts
|

A Mini Review on Medicinal Effects of Edible Bird’s Nest

Abstract: Edible bird's nest is a famous and nutritious food which is well-known among Chinese community. It is made from the saliva of swiftlets. It is consumed for various reasons, including as health tonic, complexion enhancer, asthma alleviator and immune system enhancer. It contains both macronutrients and micronutirents such as carbohydrates, glycoproteins, calcium, sodium, magnesium, zinc, manganese, iron and others. To date, a number of studies have reported on the health benefits of EBN consumption. Hence, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…As shown in Figure 4J , TeeBN mainly influenced the pathways of metabolism, organismal system, and environmental information processing pathway ( P < 0.05 and pathway impact >0), with significant influences on amino acid metabolism, the digestive system, biosynthesis of other secondary metabolites, and membrane transport. In summary, TeeBN shared many nutritional factors including vitamins, amino acids, monosaccharides, cofactors, fatty acids, phospholipids, nucleosides, and carboxylic acids [ 36 ] . Its similarity with natural EBN-I in metabolite patterns suggested that TE-based production by epithelial cells resembled the natural process.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4J , TeeBN mainly influenced the pathways of metabolism, organismal system, and environmental information processing pathway ( P < 0.05 and pathway impact >0), with significant influences on amino acid metabolism, the digestive system, biosynthesis of other secondary metabolites, and membrane transport. In summary, TeeBN shared many nutritional factors including vitamins, amino acids, monosaccharides, cofactors, fatty acids, phospholipids, nucleosides, and carboxylic acids [ 36 ] . Its similarity with natural EBN-I in metabolite patterns suggested that TE-based production by epithelial cells resembled the natural process.…”
Section: Resultsmentioning
confidence: 99%
“…EBN has antioxidant effects which could serve as a novel alternative therapy for oxidative stress-mediated neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease (PD) (Tai et al, 2017). The antioxidant capacity of EBN is higher in extracts obtained via alkaline extraction, it is speculated that the hydrolysed proteins release amino acids such as Cys, Met, His, Try and Lys with antioxidant properties (Lee et al, 2015).…”
Section: Antioxidation and Neuroprotectionmentioning
confidence: 99%
“…Manfaat kesehatan ini burung walet berperan dalam mengatasi malnutrisi, meningkatkan sistem imun dan metabolism tubuh [3]. Efek kesehatan yang menguntungkan apabila mengkonsumsi sarang burung walet sebagai antivirus, anti-oxidant, anti-diabetes, anti-penuaan, neuro-protective dan chondroprotective [4].…”
Section: Pendauluanunclassified